URGENSI MODEL PEMBELAJARAN INOVATIF DALAM MENINGKATKAN PRESTASI ANAK DIDIK - Hubbil Khair (CV. ADIBA ASIHA AMIRA, 2024)
This study aims to explore the urgency of innovative learning models in improving student achievement. Innovative learning models not only improve academic results, but also facilitate the development of critical and creative skills of students. This study uses a qualitative approach. The results of the study indicate that the urgency of innovative learning models has a positive impact on student achievement, which is reflected in innovative learning models, namely, problem-based learning models, contextual, teaching and learning models, cooperative learning models, PAKEM learning models, project-based models, e-learning models, inquiry models and technology-based models. This study is expected to provide insight for educators and policy makers in creating a more effective learning environment.Innovative Learning Models, Education, students